DOI: 10.31274/etd-180810-987
|View full text |Cite
|
Sign up to set email alerts
|

The portrayal of the nature of science in early childhood instructional materials

Abstract: Science education has a dual role for society as it seeks to help students to understand what is currently known and accepted in regards to the natural world the content as well as help students to come to understand how science works the nature of science. While both must occur simultaneously as one without the other will not lead to science literacy, explicit teaching of the nature of science (NOS) is often overlooked. Many explanations may account for this oversight, this thesis will explore the portrayal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Because elementary teachers have less content knowledge than their secondary colleagues, they are even more likely than secondary teachers to rely upon curriculum materials to define the content and experiences for science instruction. Schrauth (2009) showed that early primary materials had woefully inadequate portrayals of the nature of science, assuming that students would learn accurate NOS ideas implicitly, and even conveyed misconceptions that likely fit with teachers' documented NOS misconceptions. Since curriculum materials can serve an educative role, far more information is needed about NOS portrayals at the elementary level and the extent to which such materials are educating both teachers and students in accurate ways.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because elementary teachers have less content knowledge than their secondary colleagues, they are even more likely than secondary teachers to rely upon curriculum materials to define the content and experiences for science instruction. Schrauth (2009) showed that early primary materials had woefully inadequate portrayals of the nature of science, assuming that students would learn accurate NOS ideas implicitly, and even conveyed misconceptions that likely fit with teachers' documented NOS misconceptions. Since curriculum materials can serve an educative role, far more information is needed about NOS portrayals at the elementary level and the extent to which such materials are educating both teachers and students in accurate ways.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the presence and accuracy of the nature of science in upper elementary curriculum materials, this study was designed to address the following research questions: This study will use qualitative methods used in the Schrauth (2009) study to analyze curriculum materials published for grade 3-5 students. This study, and that of Schrauth (2009), was based on the following NOS concepts that have been commonly asserted as appropriate for K-5 students:…”
Section: Research Questions and Methodologymentioning
confidence: 99%
See 3 more Smart Citations